Coping competence and health outcomes in post-COVID: A prospective study on the role of adaptive strategies in symptom management and physical and mental health - Koller, Katharina; Herold, Regina; Morawa, Eva; Erim, Yesim (Journal of Psychosomatic Research, 2025)
Background: Post-acute sequelae of COVID-19 (PASC), characterized by persistent symptoms like fatigue, cognitive impairments, and mental health problems, requires effective coping strategies for symptom management, yet their impact on health outcomes in PASC patients remains unclear. This study examines differences in coping strategies across subgroups, changes over time, and their relationship with PASC symptoms and physical and mental health. Methods: In a prospective study, conducted at the Post-COVID Center of the University Hospital of Erlangen, patients were assessed at baseline (T0) and follow-up (T1; M = 4.46 months, SD = 2.27). Coping strategies were measured using the Patient Competence Questionnaire-2 (PCQ-2), including coping competence, religious/spiritual coping, healthy lifestyle, information-seeking, and adaptability. PASC symptom severity (PCS score), fatigue (FSS), post-exertional malaise (DSQ-PEM), and depressive symptoms (PHQ-9) were also assessed. Results: Among 339 participants (age: M = 45.51 years, SD = 11.96; 70.2 % women) coping competence improved significantly over time, while no notable changes were observed in the other factors and overall patient competence. Women scored higher than men in religious/spiritual coping, coping competence, and healthy lifestyle (all p < .001). Higher education levels were associated with higher scores in coping competence, information-seeking, and healthy lifestyle (p = .028, p = .014 and p = .012, respectively). Higher coping competence at T0 significantly predicted fewer symptoms of fatigue and depression (p = .021 and p < .001, respectively) at T1, whereas higher adaptability at T0 was associated with more severe fatigue, PEM, and depression at T1 (p < .001, p = .001 and p = .020, respectively). Conclusion: Strengthening coping competence may improve symptom management and severity in PASC patients, highlighting the need for targeted interventions. Trial registration: DRKS00033621, https://drks.de/search/de/trial/DRKS00033621
CRIS-Team Scopus Importer:2025-06-06
Keywords: Coping competence; Coping with illness; Fatigue; Long-COVID; Mental health; PASC; Post-COVID syndrome